Parameter subset reduction for imaging-based digital twin generation of patients with left ventricular mechanical discoordination - Tijmen Koopsen; Nick van Osta; Tim van Loon; Roel Meiburg; Wouter Huberts; Ahmed S. Beela; Feddo P. Kirkels; Bas R. van Klarenbosch; Arco J. Teske; Maarten J. Cramer; Geertruida P. Bijvoet; Antonius van Stipdonk; et al. (BioMedical Engineering OnLine, 2024)
Abstract Background Integration of a patient’s non-invasive imaging data in a digital twin (DT) of the heart can provide valuable insight into the myocardial disease substrates underlying left ventricular (LV) mechanical discoordination. However, when generating a DT, model parameters should be identifiable to obtain robust parameter estimations. In this study, we used the CircAdapt model of the human heart and circulation to find a subset of parameters which were identifiable from LV cavity volume and regional strain measurements of patients with different substrates of left bundle branch block (LBBB) and myocardial infarction (MI). To this end, we included seven patients with heart failure with reduced ejection fraction (HFrEF) and LBBB (study ID: 2018-0863, registration date: 2019–10–07), of which four were non-ischemic (LBBB-only) and three had previous MI (LBBB-MI), and six narrow QRS patients with MI (MI-only) (study ID: NL45241.041.13, registration date: 2013–11–12). Morris screening method (MSM) was applied first to find parameters which were important for LV volume, regional strain, and strain rate indices. Second, this parameter subset was iteratively reduced based on parameter identifiability and reproducibility. Parameter identifiability was based on the diaphony calculated from quasi-Monte Carlo simulations and reproducibility was based on the intraclass correlation coefficient ( $${ICC}$$ ICC ) obtained from repeated parameter estimation using dynamic multi-swarm particle swarm optimization. Goodness-of-fit was defined as the mean squared error ( $${χ}^{{2}}$$ χ 2 ) of LV myocardial strain, strain rate, and cavity volume. Results A subset of 270 parameters remained after MSM which produced high-quality DTs of all patients ( $${χ}^{{2}}$$ χ 2 < 1.6), but minimum parameter reproducibility was poor ( $${ICC}_{{min}}$$ ICC min = 0.01). Iterative reduction yielded a reproducible ( $${ICC}_{{min}}$$ ICC min = 0.83) subset of 75 parameters, including cardiac output, global LV activation duration, regional mechanical activation delay, and regional LV myocardial constitutive properties. This reduced subset produced patient-resembling DTs ( $${χ}^{{2}}$$ χ 2 < 2.2), while septal-to-lateral wall workload imbalance was higher for the LBBB-only DTs than for the MI-only DTs (p < 0.05). Conclusions By applying sensitivity and identifiability analysis, we successfully determined a parameter subset of the CircAdapt model which can be used to generate imaging-based DTs of patients with LV mechanical discoordination. Parameters were reproducibly estimated using particle swarm optimization, and derived LV myocardial work distribution was representative for the patient’s underlying disease substrate. This DT technology enables patient-specific substrate characterization and can potentially be used to support clinical decision making.